The genetic epidemiology and genotype-phenotype correlations among Chinese children with idiopathic and heritable pulmonary arterial hypertension - Yuan He; Qiangqiang Li; Chen Zhang; Bradley B. Keller; Yiping Shen; Hong Gu (Respiratory Research)
Abstract Objective This study aims to analyze the genetic characteristics, genotype-phenotype correlation and long-term prognosis of children with idiopathic/hereditary pulmonary arterial hypertension (IPAH/HPAH) in a Chinese tertiary medical center. Methods A retrospective review was conducted for all children with IPAH/HPAH treated at Beijing Anzhen Hospital over the past 15 years. All patients underwent genetic testing. Results In total, 170 children with IPAH/HPAH were included in the study (females n = 95, 56%), with a median age of diagnosis 6.46 (3.80, 10.70) years. The study population presented with severe conditions at baseline, with 77 patients assessed as clinically high-risk. Genetic testing identified pathogenic variants in 110 patients (64%), with BMPR2, ACVRL1, and TBX4 accounted for the main causal genes. Compared to non-carriers, carriers of pathogenic variants had a higher clinical risk at baseline (54% vs. 30%, p = 0.04). After targeted therapy, carriers experienced greater clinical deterioration (p = 0.008). The overall follow-up duration was 2.68 (1.60, 4.98) years, with the survival rate at 1-, 3-, and 5-year was 93.4%, 86.7%, and 68.6%, respectively. The prognosis of carriers was significantly worse than that of non-carriers (Log-rank p < 0.001). Multivariate Cox regression analysis indicated that pathogenic variants and higher pulmonary vascular resistance index (PVRI) and were associated with a higher risk of death. Conclusion We uncovered a higher rate of pathogenic variants in Chinese pediatric PAH, while targeted therapy improves the overall prognosis of children with PAH, patients with pathogenic variants presented with poorer response to therapy and poorer prognosis.